Development and Validation of RP-HPLC Method for the Determination of Ganciclovir in Bulk Drug and its formulations - PRAKASH S SARSAMBI,; ABHAY SONAWANE,; ABDUL FAHEEM, (International Journal of Pharma and Bio Sciences, 2010)
A simple, precise, rapid and reproducible reverse phase high performance liquid chromatographic method has been developed and validated for quantitative estimation of Ganciclovir (GCV) in bulk drug and its formulations using Acyclovir as an internal standard (IS). The chromatographic separation was achieved by using column oyster (250 x 4.6mm, 5µm) mobile phase consist of combination of triflouro acetic acid buffer and methanol at pH 2.5 in the ratio of 80:20 respectively and was pumped at 1.0 mL/min and the injection volume was 10 µL. The detection was carried out at 254 nm. Retention times were 5.823 and 7.107 min for GCV and Acyclovir (IS) respectively. Linearity of method was 12-72 µg/mL, the correlation coefficient was found to be 0.9987. The separation was performed at temperature of 300C. The method was validated according to ICH guidelines. Due to its simplicity, rapidness, high precision and accuracy the proposed HPLC method may be used for the determination of GCV in quality control samples and its formulations with out interference of excipients.